Influencing factors and survival rates in immediate vs. delayed dental implant placement: a six-year retrospective analysis - Cheng, Yanfei; Lai, Zhifen; Yu, Weiguang (Frontiers in Dental Medicine, 2025)
ObjectiveThis retrospective cohort study aimed to compare survival rates between immediate (≤24 h post-extraction) and delayed (3–4 months post-extraction) dental implants and to identify patient- and site-specific risk factors for implant failure, with emphasis on anatomical site, sex, and osteoporosis.MethodsWe analyzed 1,500 implants (300 immediate, 1,200 delayed) from patients treated at the Guangdong Provincial Hospital of Traditional Chinese Medicine (2005–2023). Kaplan–Meier analysis evaluated cumulative survival rates over 72 months, with Cox regression modeling to assess predictors of failure. Propensity score matching (PSM) addressed baseline covariate imbalances.ResultsDelayed implants exhibited significantly higher survival rates than immediate implants at 72 months (81.1% vs. 53.2%, p < 0.0001). Survival divergence intensified after 24 months, with delayed implants retaining 979 patients at risk vs. 202 for immediate implants. Mandibular sites consistently outperformed maxillary sites in both strategies (delayed: 88.5% vs. 72.2%; immediate: 70.5% vs. 40.7%, p < 0.0001). Male sex (HR: 1.64, 95% CI: 1.28–1.88; p < 0.001) and osteoporosis (HR: 2.50, 95% CI: 1.17–4.52; p = 0.024) emerged as independent risk factors, while tobacco use, diabetes, and hypertension showed no significant associations. PSM resolved most baseline imbalances, with post-matching standardized mean differences (SMD) <0.1 for key covariates.ConclusionsDelayed implantation at 3–4 months post-extraction provides superior intermediate-term survival, particularly in mandibular sites. Male patients and individuals with osteoporosis face elevated failure risks, warranting tailored clinical protocols. While both strategies remain viable, delayed placement is recommended for high-risk populations to optimize long-term outcomes.